Population genetic structure of a Chihuahuan Desert endemic mammal, the desert pocket gopher, Geomys arenarius - Russell S. Pfau; Ashley N. Kozora; Ana B. Gatica‐Colima; Philip S. Sudman (Ecology and Evolution, 2023)
Abstract The biogeographic history of the Chihuahuan Desert is complex, driven by numerous physiographic events and climatic changes. This dynamic history would have influenced the flora and fauna of the region including the desert pocket gopher, Geomys arenarius, a subterranean rodent endemic to the northern Chihuahuan Desert. G. arenarius is restricted to sandy soils and are considered to have a disjunct distribution. Two subspecies are recognized: G. a. arenarius and G. a. brevirostris. We used multilocus nuclear (amplified fragment length polymorphisms) and mitochondrial DNA (ND2) sequence data to uncover patterns of genetic diversity within and among populations of G. arenarius. We evaluated correspondence of genetic patterns to traditionally accepted subspecies boundaries, mapped the distribution of potentially suitable soils to identify barriers or corridors to dispersal and to guide future survey efforts, provided evidence that could be used to recognize distinct population segments, and quantified genetic diversity within populations. Both datasets were largely concordant and demonstrated hierarchical patterns of genetic divergence. The greatest divergence was consistent with the two recognized subspecies. Mapping of potentially habitable soils revealed likely barriers to dispersal contributing to the allopatric pattern of geographic distribution and areas, which may be occupied by G. arenarius but not yet documented. Because G. arenarius is restricted to soils with high sand content, and these habitable soils are disjunct within the region occupied by this species, historical factors that impacted soil deposition and deflation likely contributed to the observed patterns of genetic divergence. Genetic diversity was higher within populations of the southern subspecies (G. a. arenarius) compared to G. a. brevirostris. This may be due to a greater availability of continuous suitable soils within the range of G. a. arenarius or higher density due to greater food availability (currently or historically)—both of which could allow for a higher effective population size.